The role of EARLY FLOWERING 3 and PHYTOCHROME B interaction in response to red light in Arabidopsis thaliana - Queiroz, Marina Viana (2022)
The circadian clock is a complex internal mechanism that is responsible for translating environmental cues into physiological and metabolical changes to increase plant fitness. Due to its complexity, there is a gap in the knowledge between light perception and light response, moreover, which genes are operating and how it happens. Previously work has shown that PHYTOCHROME B acts to stabilize EARLY FLOWERING 3, however, this study could be partially compromised by the presence of metabolites from photosynthesis, internal cues that are capable of resetting the clock. This work aims to understand the role of EARY FLOWERING 3 and PHYTOCHROME B interaction in the response to red light in Arabidopsis thaliana under photosynthesis inhibition. To do that it was used the transgenic lines E1.06, elf3-2, YHB, YHB ABCDE, and phyB ABCDE. Arabidopsis seeds were sown in MS-agar and MS-agar with 1% Sucrose plates and left in the growth chamber for 5 days at 22°C under 12:12 L/D cycles of 60 μmol m-2 s-1 white LED light before circadian imaging. After 5 days, seedlings were transferred to MS and Sucrose plates and sprayed with a solution containing luciferin. The photosynthesis was inhibited by soda lime, 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) and dibromothymoquinone (DBMIB) in both MS and Sucrose plates. Circadian imaging was completed over 5 days using an Andor iKon-M CCD camera controlled by μManager and data were processed using ImageJ. Patterns of luciferase activity were fitted to cosine waves using fast Fourier transformnonlinear least squares (FFT-NLLS) to estimate circadian period length. ELF3 is not necessary for YHB to induce photomorphogenesis. The conclusions are ELF3 protein modulates photosynthetic inputs into the circadian system and together with phytochrome B definitely has a role in the red- light response and temperature regulation. However, is not possible to understand the contribution of ELF3 to temperature entrainment yet. Moreover, the superior performance of YHB ABCDE in the experiments under temperature variation, could expand the hypothesis about the application of phytochrome B in temperature adaptation serving as a key mediator of information to the circadian clock.